2014
DOI: 10.1016/j.clon.2013.09.004
|View full text |Cite
|
Sign up to set email alerts
|

A National Audit of Current Cardiac Device Policies from Radiotherapy Centres across the UK

Abstract: Aims: The number of patients with cardiac implantable electronic devices (permanent pacemakers and implantable cardioverter defibrillators) undergoing radiotherapy treatment is increasing. The aims of this audit were to establish current UK practice regarding the management of patients with implanted cardiac devices undergoing radiotherapy and to compare this practice with current 'gold standard' evidence-based guidelines. Materials and methods: All UK radiotherapy departments were contacted and asked to provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 13 publications
(21 reference statements)
2
8
0
Order By: Relevance
“…A mere 35% monitor the patient during treatment and only 20% of the clinics perform in vivo dose measurements regularly. Similar inconsistent or insufficient practices were observed by Lester et al based on a survey across the United Kingdom, and by Soejima et al, in a survey of centers in Japan. Gossman et al, in a retrospective physicians’ survey on treatment approach, delivery and follow‐up for management of RT patients with CIEDs, concluded that most radiation oncologists were unfamiliar with the recommended standard of practice by the AAPM, and the involvement of the medical physicist (MP) with patient management, finding both to be insufficient.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…A mere 35% monitor the patient during treatment and only 20% of the clinics perform in vivo dose measurements regularly. Similar inconsistent or insufficient practices were observed by Lester et al based on a survey across the United Kingdom, and by Soejima et al, in a survey of centers in Japan. Gossman et al, in a retrospective physicians’ survey on treatment approach, delivery and follow‐up for management of RT patients with CIEDs, concluded that most radiation oncologists were unfamiliar with the recommended standard of practice by the AAPM, and the involvement of the medical physicist (MP) with patient management, finding both to be insufficient.…”
Section: Introductionsupporting
confidence: 80%
“…In case this is not known prior to consultation, the patient should be asked during the first visit to the RT facility. The patient (or patient’s legal representative) consent should be obtained in which that person is educated and notified about the potential adverse effects of RT on CIEDs and that an ICD might be deactivated during RT …”
Section: Patient Management and Recommendationsmentioning
confidence: 99%
“…The fraction of RT courses leading to an additional PM/ICD evaluation was relatively low. Lester et al recently reported that 76% of RT departments in the UK require cardiology assessment in this patient group according to their policies. Meanwhile, back in 2004, only 37% of RT departments in North America had a practice of consulting cardiologists during RT in PM/ICD patients …”
Section: Discussionmentioning
confidence: 99%
“…Ionizing radiation used in cancer external beam radiotherapy (RT) can damage electronic heart rhythm devices, potentially threatening the safety of the patient . The number of patients with a pacemaker (PM) or an implantable cardioverter defibrillator (ICD) undergoing RT is assumed to be increasing . However, very little is known about the exact size of this population and temporal developments in its magnitude.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation